Perancangan Website untuk Meningkatkan Brand Awareness dan Penjualan : Studi Kasus pada UMKM Taste.ki - Zaid, Nurmalianti; Jamil, Muhammad; Aris, Valentino (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
Taste.ki MSME, a café in Makassar, faces challenges from intense competition and an suboptimal digital marketing strategy, relying only on Instagram without a consistent content strategy. This study aims to design a website integrated with Instagram to strengthen Brand Awareness and increase sales. The research employed the Four-D method (Define, Design, Develop, Disseminate), and the website was designed using the Wordpress CMS. The results indicate that the website design was successfully implemented. The integration of the website with Instagram significantly improved Brand Awareness, evidenced by a Brand Recognition achievement of 88% and Brand Recall of 94%. Furthermore, this digital strategy positively impacted Taste.ki MSME's sales, showing an increase of 79.20%. This improvement confirms the crucial role of a website as an information hub and conversion channel in an MSME's digital marketing strategy to compete effectively in the digital era.